A Note on the Effect of Nitrogen and Irrigation Levels on Growth and Fodder Yield of Barley - Faroda, A S (Annals of Arid Zone, 2016)
(i) Application of 30 Kg N/ha irrespective of its source increased the plant height and green fodder yield per hectare over unmanured control. (ii) Five irrigations were found slightly better in terms of green foClder yield per aectare as compa red to lower irrigation levels